Assessment of a colorectal Cancer screening project using faecal occult blood test (FOBT) kit in Penang state, Malaysia - Alaydrus, Lely Lubna (2014)
Incidence of colorectal cancer (CRC) has been increasing in many countries due to changes in life style. In Malaysia, CRC is the second most common cancer with the highest incidence among the Chinese ethnic group. Periodic screening for CRC with faecal occult blood test kit (FOBT) has been shown to reduce the mortality and morbidity from this disease. The objective of this study was to assess a CRC screening project using FOBT kit in Penang, Malaysia. A total of 970 FOBT kits were distributed between June and November 2009 during CRC public health talks. Data was collected using self-administered questionnaires and telephone interviews. Statistical analyses were carried out using PASW version 18 for descriptive statistics as well as for the binary logistic regression analyses to determine associated factors for CRC knowledge and return of FOBT. A total of 617 participants completed the first questionnaire with a response rate of 63.6 %. Few (3.8 %) reported encountering difficulties in doing the FOBT. The level of awareness of stool examination and knowledge of CRC were poor among participants. The factors associated with poor knowledge of CRC were low education (OR=3.07; 95%CI: 2.01-4.70) and not having family history of cancer (OR=1.71; 95%CI: 1.16-2.52). Older age (OR =3.31; 95%CI: 2.09-5.23), Chinese ethnicity (OR=2.35; 95%CI: 1.32- 4.19) and higher education (OR=2.26; 95%CI:1.49- 3.42) were factors associated with the return of FOBT kit.